Mobility in Transition Migration Patterns after EU Enlargement - Glorius, Birgit; Grabowska, Izabela 1978-; Kuvik, Aimee (IMISCOE Research, 2013)
Ten central and eastern European countries, along with Cyprus and Malta, joined the European Union in two waves between 2004 and 2007. This volume presents new research on the patterns of migration that resulted from the EU's enlargement. The contributors identify and analyze several new groups of migrants, notably young people without family obligations or clear plans for the future. Including case studies on migrants from Poland, Romania, Hungary, and Latvia-as well as on destination countries such as the United Kingdom and Germany-the resulting collection insightfully points towards future migration trends and sets guidelines for further research